Polityka językowa i tożsamość kulturowa mniejszości - Boroń, Aleksandra (Studia Edukacyjne, 2021)
The text aims to draw attention to the language policy involved in the processes of constructing the cultural identity of minorities. Discussion focuses on the two basic dichotomies of assimilationism-isolationism and empowerment-objectification and indicates selected aspects of language policy and educational practices in France, China and Israel.